Infusion of an acidified ethanolic—dextrose solution enhances urinary ammonium excretion and increases acid resilience in non—mechanically ventilated acidotic rabbits - Walsh, Patrick A. (Frontiers in Physiology, 2022)
Hitherto, the rabbit has long been known to have a very poor tolerance to non – volatile acid. In this study, we tested our hypothesis that acid resilience in the acidotic rabbit can be increased by enhancing the plasma availability of a naturally occurring volatile fatty acid, namely acetate. To ascertain the relative merits of the respiratory and renal systems in contributing to that resilience, we conducted our studies in non – ventilated and mechanically ventilated acidotic animals. Using ethanol as a feeder of acetate, and to counteract the antidiuretic effects of surgical interventions, we induced acidosis in anaesthetised rabbits, by intravenously infusing an acidified ethanolic dextrose solution. We observed very potent respiratory regulation of arterial blood pH coupled with a notable renal response by way of a 25-fold increase in urinary ammonium excretion in the non – ventilated group. In contrast, arterial blood pH plummeted much more rapidly in the mechanically – ventilated animals, but the compensated renal response was enormous, in the form of an 85 -fold increase in urinary ammonium output. Despite this significant adaptive renal response, the non -mechanically ventilated group of rabbits showed the greater acid resilience. This was attributed to an acetate stimulated flux through a series of metabolic pathways, generating supplementary buffer in the form of bicarbonate and ammonia, complemented by a robust respiratory response. In conclusion, given an adequate supply of acetate, the rabbit has shown that it has both the respiratory and renal capacities to adapt to systemic acid challenges of a magnitude, not previously reported.